2000
DOI: 10.1088/0953-2048/13/5/309
|View full text |Cite
|
Sign up to set email alerts
|

Long length PIT conductors realized by rectangular deformation route

Abstract: Alcatel pursues the development of multifilamentary Bi-2212 and Bi-2223 tape conductors by the rectangular deformation route. It is shown by a simple cost evaluation that the Bi-2212 conductor represents today the optimum cost versus performance solution for applications in the intermediate temperature range 20-30 K. This interest in the Bi-2212 conductor is related: (1) to higher current density in the intermediate temperature range and (2) to the higher stability range at the formation temperature of the sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Critical current densities as high as have been found in Ag/Bi2212 tapes at 4.2 K and 10 T [3]. It has been demonstrated that degrades around 20% when the applied magnetic field increases from 10 T to 30 T [4].…”
Section: Introductionmentioning
confidence: 76%
“…Critical current densities as high as have been found in Ag/Bi2212 tapes at 4.2 K and 10 T [3]. It has been demonstrated that degrades around 20% when the applied magnetic field increases from 10 T to 30 T [4].…”
Section: Introductionmentioning
confidence: 76%
“…Bi2212 multifilament tapes were fabricated by the well established powder in tube (PIT) technique. Details of the process can be found elsewhere [7].…”
Section: Methodsmentioning
confidence: 99%
“…The tape comprises 78 filaments embedded in a Ag-Mg (0.2% Mg) sheath. Details of this process can be found elsewhere [12].…”
Section: Dynamic Heat Process Under a Magnetic Fieldmentioning
confidence: 99%